(Effects of Methods and Distillation Time of " Kapolaga " (Amomum cardamomum Wild.) on The Yield and Chemical Properties of The Oil Produced. - Sumarsi -; Sri Harjanto; Untari Pujiastuti (Warta Industri Hasil Pertanian, 1989)
The method was steam distillation and water and steam distillation, whereas the duration was, 4,5,6,7 and 8 hours. It was found out that the highest yield (5,85%) was obtained from 6 hours steam distillation. The analysis of the oil showed that steam distillation method gave lower acid number, but water and steam distillation for 4 hours resulted in highest cineolcontent.